Smarandache Ruled Surfaces according to Darboux Frame in E3 - Soukaina Ouarab (Journal of Mathematics)
This paper presents a new approach of constructing special ruled surfaces and aims to study their developability and minimalist conditions. Our concept opens opportunities for application in engineering, surface modeling, and architectural design. The principle of our study is to introduce the original definitions of Smarandache ruled surfaces according to Darboux frame of a curve lying on an arbitrary regular surface in E3. It concerns Tg-Smarandache ruled surface, Tn-smarandache ruled surface, and gn-Smarandache ruled surface. New theorems giving necessary and sufficient conditions for those surfaces to be developable and minimal are investigated. Finally, an example with illustrations is presented.